Sociology of Education - Roberts, Keith (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Education is an extremely important institution in America. It influences the lives of people at a very impressionable age, it shapes the self-image of its students in ways that impact them the rest of their lives, it is often the largest single employer in many communities and has an enormous economic function in the community, and it is given a pivotal role in the mythology of America that says that anyone can move to a higher social class if they take the proper steps for achievement. Next to the family, this is the institution with which each of you have had the most significant and prolonged experience. In this course, we will see how sociology conducts research and analyses schools and educational processes. In so doing, students will further expand their ability to exercise the sociological imagination.